Peripartum cardiomyopathy co-existing with severe preeclampsia complicated by AKI - Tonmoy Das; Alaka Goswami; Himleena Gautam; Maileng Tham; Anupama Hajong; Nahid Farzin; Nilanjana Das (Barpeta Obstetrics and Gynaecological Society, 2019)
Peripartum cardiomyopathy is a rare idiopathic cardiac disease occurring in pregnancy and puerperium. Studies have shown that women with preeclampsia have a higher risk of developing peripartum cardiomyopathy. In this report we present a case of a 3rd trimester pregnancy with severe preeclampsia with acute kidney injury who was diagnosed with peripartum cardiomyopathy. Supportive management was done with a multidisciplinary approach. Caesarean section was done, an IUGR but healthy baby was delivered and the patient recovered gradually.